Stilte in de klas Een geschiedenis van de pedagogische omgang met stilte op school - Verstraete, Pieter (Leuven University Press, 2022)
Silence runs like a thread through the history of the school. In past centuries, countless teachers have urged children to be quiet. There have also been many publications in which educational authors have reflected on the value of silence for education. In this book, Pieter Verstraete explores the history of the pedagogical significance of silence using previously unexplored archival material. Have you always wanted to know where the preference for classroom silence comes from? Do you wonder why we teach reading in silence today and if it was always like that? Do you want to know how quiet and shy students used to be treated? Or are you curious why Maria Montessori thought silence classes were so important? This book fascinatingly introduces you to the multi-voiced sound of silence in the history of parenting and education.